Switched Reluctance Motor Initial Design for Electric Vehicle using RMxprt - Kasrul Abdul Karim; Nurfaezah Abdullah; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
This paper presents a design and development of 8/6 switched reluctance motor for small electric vehicle using analytical method. The absent of permanent magnet, inherent fault tolerance capabilities, simple and robust construction make this motor become more attractive for small electric vehicle application such as electric scooter and go-kart. The switched reluctance motor is modelled using analytical formula in designing process. Later, the designed model is analyzed using ANSYS RMxprt software. In order to achieve 5kW power rating and to match with the design requirement, the switched reluctance motor model has been analyzed using RMxprt tools for the preliminary parameters design process. This tools is able to predict the output performance of motor in term of speed, flux linkage characteristic, output torque and efficiency.